2017
DOI: 10.1016/j.envsoft.2016.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Exploring snow model parameter sensitivity using Sobol' variance decomposition

Abstract: This study advances model diagnostics for snowmelt-based hydrological systems using Sobol' sensitivity analysis, illuminating parameter sensitivities and contrasting model structural differences. We consider several distinct snow-dominated locations in the western United States, running both SNOW-17, a conceptual degree-day model, and the Variable Infiltration Capacity (VIC) snow model, a physically-based model. Model performance is rigorously evaluated through global sensitivity analysis and a temperature war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…The energy exchange at the snow‐ground interface is usually small and thus neglected in modeling. Our analyses focused on five parameters identified in previous studies as important to modeling snowpack dynamics (Cristea et al, ; Houle et al, ; Koivusalo & Heikinheimo, ; Lynch et al, ; Malik et al, ; Pavelsky et al, ; Rajagopal & Harpold, ; Xue et al, ). The five parameters are fresh snow albedo ( α max ); the albedo decay coefficient during snow accumulation ( λ A ); the albedo decay coefficient during melt ( λ M ); and the precipitation partitioning threshold temperatures, including the minimum temperature for precipitation to be in the form of rain ( T R , in °C) and the maximum temperature for precipitation to be in the form of snow ( T S , in °C).…”
Section: Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The energy exchange at the snow‐ground interface is usually small and thus neglected in modeling. Our analyses focused on five parameters identified in previous studies as important to modeling snowpack dynamics (Cristea et al, ; Houle et al, ; Koivusalo & Heikinheimo, ; Lynch et al, ; Malik et al, ; Pavelsky et al, ; Rajagopal & Harpold, ; Xue et al, ). The five parameters are fresh snow albedo ( α max ); the albedo decay coefficient during snow accumulation ( λ A ); the albedo decay coefficient during melt ( λ M ); and the precipitation partitioning threshold temperatures, including the minimum temperature for precipitation to be in the form of rain ( T R , in °C) and the maximum temperature for precipitation to be in the form of snow ( T S , in °C).…”
Section: Methods and Datamentioning
confidence: 99%
“…Recent studies (Chen et al, ; Essery et al, ; Etchevers et al, ; Feng et al, ; He et al, ; Houle et al, ; Koivusalo & Heikinheimo, ; Mendoza et al, ; Wayand et al, ) have explored the impact of model complexity on model performance and found that the model performance can be very dependent on model application. Feng et al () compared the performance of five physics‐based Land Surface Models (LSMs) with different physical complexities of snow processes on snow simulations at three experimental sites in north‐central Colorado.…”
Section: Introductionmentioning
confidence: 99%
“…, Houle et al. ). Due to variation in topography, vegetation cover, and wind strength, winter snow cover in alpine forests is often patchy, with areas of distinctly different snow depth.…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing number of studies have shown that litter decomposition occurs primarily in winter in forest ecosystems (Gavazov 2010, Atkins et al 2017. Authors have attributed this contrasting pattern to snow's insulating properties, which produces a relatively stable environment for decomposers, as well as strong nutrient leaching during snowpack formation and melting (Lemma et al 2007, Zeidler et al 2014, Houle et al 2017). Due to variation in topography, vegetation cover, and wind strength, winter snow cover in alpine forests is often patchy, with areas of distinctly different snow depth.…”
Section: Introductionmentioning
confidence: 99%
“…The process has inherent uncertainty, and measures of uncertainty commonly accompany any modeling analysis [e.g., Pappenberger and Beven , ; Montanari , ; Beven , ; Nearing et al ., ]. Sensitivity analysis is conducted to understand the relation between inputs and outputs and to obtain insights in what often is a complicated model input‐output mapping [ Hill and Tiedeman , ; Saltelli et al ., ; Rosero et al ., ; Mendoza et al ., ; Norton , ; Hill et al ., ; Pianosi et al ., ; Razavi and Gupta , ; Markstrom et al ., ; Houle et al ., ]. These discoveries help the analyst to use simulated values appropriately in planning, risk assessment, and decision support.…”
Section: Introductionmentioning
confidence: 99%